2022
DOI: 10.1186/s12872-022-02889-y
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors among people with drug-resistant tuberculosis in Uganda

Abstract: Background Tuberculosis (TB) and its risk factors are independently associated with cardiovascular disease (CVD). We determined the prevalence and associations of CVD risk factors among people with drug-resistant tuberculosis (DRTB) in Uganda. Methods In this cross-sectional study, we enrolled people with microbiologically confirmed DRTB at four treatment sites in Uganda between July to December 2021. The studied CVD risk factors were any history o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
(34 reference statements)
0
2
2
1
Order By: Relevance
“…On the contrary, the prevalence of hypertension among patients with drug-resistant tuberculosis in Uganda was significantly higher, at 40.6%, 26 almost double our observed prevalence. This considerable variability in hypertension levels highlights differences in risk exposures.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…On the contrary, the prevalence of hypertension among patients with drug-resistant tuberculosis in Uganda was significantly higher, at 40.6%, 26 almost double our observed prevalence. This considerable variability in hypertension levels highlights differences in risk exposures.…”
Section: Discussioncontrasting
confidence: 69%
“…It is a vital finding that none of the faculty were smoking at the time of the study, and this is contrary to findings from an urban Ugandan HIV clinic at 9.7%, 43 among drug-resistant tuberculosis patients in Central, Western, Northern and Eastern Uganda at 36.3% 26 and among patients in Western Kenya at 5%. 22 Tobacco cessation information is readily available in Ugandan urban settings and given that Makerere University has a zero-smoking policy, it could be the explanation for no participants being current smokers relative to studies conducted among the general population.…”
Section: Discussioncontrasting
confidence: 62%
“…Un estudio realizado en Uganda sobre factores de riesgo cardiovasculares entre personas con tuberculosis resistente a medicamentos que incluyó 212 participantes encontró que el 92% de la población con tuberculosis tenía ≥ 1 factor de riesgo de enfermedad cardiovascular: la dislipidemia (62,5%; 55,4-69,1), hipertensión (40,6%; 33,8-47,9), obesidad central (39,3%; 32,9-46,1), tabaquismo (36,3%; 30,1-43,1), indice de masa corporal (IMC) elevado (8,0%; 5,0-12,8) y diabetes mellitus (6,5%; 3,7-11,1) resaltaron como los principales (26) . Esta interrelación de factores de riesgo podría explicar la coexistencia de eventos cardiovasculares adversos y TB.…”
Section: Factores De Riesgo Relacionados Con Enfermedad Cardiovascula...unclassified
“…A study conducted in Uganda on cardiovascular risk factors among people with drug-resistant tuberculosis, which included 212 participants, found that 92% of the population with tuberculosis had ≥ 1 cardiovascular disease risk factor: dyslipidemia (62.5%; 95% CI [confidence interval]: 55.4-69.1), hypertension (40.6%; 95% CI: 33.8-47.9), central obesity (39.3%; 95% CI: 32.9-46.1), smoking (36.3%; 95% CI: 30.1-43.1), elevated body mass index (BMI) (8.0%; 95% CI: 5.0-12.8), and diabetes mellitus (6.5%; 95% CI: 3.7-11.1) were highlighted as the main ones 26 . This interrelation of risk factors could explain the coexistence of adverse cardiovascular events and TB.…”
Section: Introductionmentioning
confidence: 99%
“…2 Furthermore, cross-sectional studies have shown that people with TB have a high prevalence of risk factors for CVD among people with active TB. 3,4 However, prospective studies assessing the CVD risk trajectories among people after they have completed TB treatment are scarce as it may require a long follow-up period.…”
Section: Introductionmentioning
confidence: 99%